2009
DOI: 10.1007/s11046-009-9194-8
|View full text |Cite
|
Sign up to set email alerts
|

Pseudocercospora griseola Causing Angular Leaf Spot on Phaseolus vulgaris Produces 1,8-Dihydroxynaphthalene-Melanin

Abstract: Pseudocercospora griseola is the causal agent of angular leaf spot of common bean (ALS). It has undergone parallel coevolution with its host and two major groups have been defined, "Andean" (P. griseola f. griseola) and "Mesoamerican" (P. griseola f. mesoamericana). The aim of this study was to analyze the nature and the level of the dark pigment synthesized by the representatives of each group. After 21 days of incubation on potato dextrose agar medium, P. griseola f. griseola isolate S3b developed colonies w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
13

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(37 citation statements)
references
References 34 publications
0
19
0
13
Order By: Relevance
“…These polymeric substances might have a biological role such as virulence and/or survival against environmental stress factors (Bell and Wheeler 1986;Cooke and Whipps 1993;Chaskes et al 2008;Onofri et al 2008;Singaravelan et al 2008;Taborda et al 2008). Saparrat et al (2009) showed that Pseudocercopora griseola synthesizes DHN-melanins, a process that was inhibited by tricyclazole. Here, we confirmed that this inhibition leads to a reduction in fungal growth and pigmentation.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These polymeric substances might have a biological role such as virulence and/or survival against environmental stress factors (Bell and Wheeler 1986;Cooke and Whipps 1993;Chaskes et al 2008;Onofri et al 2008;Singaravelan et al 2008;Taborda et al 2008). Saparrat et al (2009) showed that Pseudocercopora griseola synthesizes DHN-melanins, a process that was inhibited by tricyclazole. Here, we confirmed that this inhibition leads to a reduction in fungal growth and pigmentation.…”
Section: Discussionmentioning
confidence: 99%
“…Concomitantly with this, the reddish pigment was released. Based on all these evidences, Saparrat et al (2009) hypothesized that the reddish pigments might be the soluble compounds released from fungal cultures grown in the presence of tricyclazole, which might be intermediate metabolites of melanin. Such a reduction in melanin synthesis, at least at certain concentrations of the inhibitor, affected mycelial growth; therefore, the melanin level in fungal wall may also be a determining factor in the organization of cell structure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations